A lanthanide-functionalized covalent triazine framework as a physiological molecular thermometer. Issue 20 (28th April 2021) - Gohari Derakhshandeh, Parviz; Abednatanzi, Sara; Bourda, Laurens; Dalapati, Sasanka; Abalymov, Anatolii; Meledina, Maria; Liu, Ying-Ya; Skirtach, Andre G.; Van Hecke, Kristof; Kaczmarek, Anna M.; Van Der Voort, Pascal
Abstract : Development of a sensitive, reusable, water-dispersible and non-toxic lanthanide-functionalized covalent triazine framework as a molecular thermometer for biological thermometric applications. Abstract : Crystalline covalent triazine frameworks (CTFs) with intrinsic porosity and high stability are an excellent platform for engineering luminescence properties, as their building blocks and guest ions are all important factors in light emission. Herein, a highly crystalline bipyridine-based CTF (Bipy-CTF) is synthesized under mild conditions. The controlled tethering of lanthanide ions (Ln = Eu 3+ and Tb 3+ ) onto Bipy-CTF combined with selective photoexcitation results in a ratiometric luminescent thermometer (LnCTF). This LnCTF thermometer exhibits an excellent linear response in the solid state over a wide range of temperatures (200–340 K), with a temperature uncertainty below 0.2% and very good reusability (up to 98.5% repeatability). Moreover, the suspended material in water shows a temperature sensitivity down to 253 K (−20 °C), which is a very important finding for monitoring the physiological processes within biological and biochemical systems during freezing/defrosting treatment with precise temperature measurements. We also studied and confirmed the low cytotoxicity of the LnCTF towards cells thereby opening prospects for future in vivo applications. This work thus highlights a new application of LnCTF materials as ratiometric luminescent molecular thermometers with excellent sensitivity in the physiological temperature range.